Liver fibrosis and CD206+ macrophage accumulation are suppressed by anti-GM-CSF therapy - Tan-Garcia, Alfonso; Lai, Fritz; Yeong, Joe Poh Sheng; Irac, Sergio E.; Ng, Pei Y.; Msallam, Rasha; Lim, Jeffrey Chun Tatt; Wai, Lu-En; Tham, Christine Y.L.; Choo, Su P.; Lim, Tony; Young, Dan Y.; et al. (JHEP reports, 2020)
Chronic liver inflammation leads to fibrosis and cirrhosis and is associated with an accumulation of intrahepatic TNFα-secreting CD206+ macrophages, which may participate in maintaining chronic liver disease in a GM-CSF-dependent manner. We aimed to elucidate the exact role of GM-CSF in the development and progression of chronic liver disease. Liver immunohistochemistry and serum quantification were performed in patients with viral and non-viral-related liver disease to compare CD206+ monocyte/macrophages, fibrosis and GM-CSF. This was followed by functional validations in vitro and in vivo in humanised mice. Using multiplex immunofluorescence and histo-cytometry, we show that highly fibrotic livers had a greater density of CD206+ macrophages that produced more TNFα and GM-CSF in the non-tumour liver regions of patients with hepatocellular carcinoma (n = 47), independent of aetiology. In addition, the absolute number of CD206+ macrophages strongly correlated with the absolute number of GM-CSF-producing macrophages. In non-HCC chronic HCV+ patients (n = 40), circulating GM-CSF levels were also increased in proportion to the degree of liver fibrosis and serum viral titres. We then demonstrated in vitro that monocytes converted to TNFα-producing CD206+ macrophage-like cells in response to bacterial products (lipopolysaccharide) in a GM-CSF-dependent manner, confirming the in vivo normalisation of serum GM-CSF concentration following oral antibiotic treatment observed in HBV-infected humanised mice. Finally, anti-GM-CSF neutralising antibody treatment reduced intrahepatic CD206+ macrophage accumulation and abolished liver fibrosis in HBV-infected humanised mice. While the direct involvement of CD206+ macrophages in liver fibrosis remains to be demonstrated, these findings show that GM-CSF may play a central role in liver fibrosis and could guide the development of anti-GM-CSF antibody-based therapy for the management of patients with chronic liver disease. Liver fibrosis is a major driver of liver disease progression. Herein, we have shown that granulocyte-macrophage colony-stimulating factor (GM-CSF) plays an important role in the development of liver fibrosis. Our findings support the use of anti-GM-CSF neutralising antibodies for the management of patients with chronic liver disease resulting from both viral and non-viral causes. [Display omitted] •GM-CSF and TNFα producing CD206+ macrophages accumulate in human fibrotic liver•Serum GM-CSF is increased in HCV+ patients with higher liver fibrosis•GM-CSF drives monocyte to CD206+ macrophage conversion•Anti-GM-CSF therapy suppresses liver fibrosis and CD206+ macrophage accumulation